Relation between Burnout and Psychosocial Factors in Health Care Providers and Family Caregivers of Patients with Cancer - D. Asha; G. Padmaja; C. Raghavendra Rao (Indian Journal of Medical and Paediatric Oncology)
Introduction Burnout has been widely studied among oncology health care providers such as nurses and doctors. However, it is a less explored but highly prevalent factor in family caregivers of patients with cancer.